Design of a low-cost multiple output switch mode power supply - Xiao, Yueyi (Nanyang Technological University, 2020)
Switch Mode Power Supply (SMPS) is an electronic power supply that incorporates a switching regulator to convert electrical power efficiently with voltage and current changing. Comparing with linear power system, SMPS varies the ratio of switches' on-to-off time to achieve the voltage regulation. SMPS minimizes the wasted energy, that means higher power conversion efficiency. This is an important advantage of Switch Mode Power Supply. SMPS is used in the final year project, ‘Design of a Low-Cost Multiple Output Switch Mode Power Supply’. This report introduces the final year project. The main content covers the whole progress of building the project, encountered problems, future works and so on.